2012
DOI: 10.1002/tox.21822
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of technical and commercial formulations of methamidophos on sperm quality and DNA integrity in mice

Abstract: Methamidophos (MET), widely used in developing countries, is a highly neurotoxic organophosphate pesticide that has been associated with male reproductive alterations. Commercial formulations of pesticides used by agricultural workers and urban sprayers are responsible for thousands of intoxications in developing countries and may not have the same effects as active pure ingredients. Therefore, we compared effects of MET technical (METt) and commercial (METc) grades on sperm quality and DNA integrity. Male mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(53 reference statements)
0
5
0
1
Order By: Relevance
“…Besides being one of the metabolic products of acephate, MT is a systemic insecticide and acaricide. It is still used in developing countries, on some crops such as wheat, soybeans, potatoes, citrus fruits, cotton, and maize (Maroni et al, ; Araoud et al, ; Lugokenski et al, ; Uriostegui‐Acosta et al, ). World Health Organization (WHO) classified the technical product as Class 1B “Highly Hazardous,” and an Acceptable Daily Intake (ADI) of 0.004 mg/kg body weight was established by the Joint Meeting on Pesticide Residues (Maroni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides being one of the metabolic products of acephate, MT is a systemic insecticide and acaricide. It is still used in developing countries, on some crops such as wheat, soybeans, potatoes, citrus fruits, cotton, and maize (Maroni et al, ; Araoud et al, ; Lugokenski et al, ; Uriostegui‐Acosta et al, ). World Health Organization (WHO) classified the technical product as Class 1B “Highly Hazardous,” and an Acceptable Daily Intake (ADI) of 0.004 mg/kg body weight was established by the Joint Meeting on Pesticide Residues (Maroni et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…fungicide carbendazim appears to target pachytene spermatocytes and spermatozoa at step 14 of spermatid differentiation at the time of first exposure [31]. Damage to the sperm DNA of mice treated intraperitoneally with MET at doses of 3.75-7.0 mg.kg −1 for 4 days has been observed [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses showed that MET administration caused significant epididymal changes. In fact, Urióstegui-Acosta et al [16] reported that the epididymis and epididymal sperm cells are targets of MET toxicity. It is possible, therefore, that the sperm transit reduction in the caput/ corpus epididymis in MET-treated mice in the short-term exposure group is a result of excess ACh in mAChR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estos compuestos son ampliamente utilizados en México y actualmente el GLA es uno de los herbicidas más empleados en algunas áreas del país, representando un problema de salud pública (Pérez-Herrera et al 2008, Rojas-García et al 2011, Urióstegui-Acosta et al 2014b. El GLA ha sido estudiado por sus efectos embriogénicos, dismorfogénicos y teratogénicos, así como por su capacidad de inducir partos prematuros y abortos en hembras expuestas experimentalmente (IPCS, 1999, Schulte-Hermann et al 2006.…”
Section: Discussionunclassified